MORPHOLOGICAL CHANGES IN THE LARGE INTESTINE UNDER THE INFLUENCE OF 70% CONCENTRATION OF ACETIC ACID WERE DETERMINED (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
Acetic acid poisoning is one of the most common types of household poisoning not only in the Republic of Uzbekistan, but also in the CIS countries [1,4]. This is due to its widespread availability and constant use in the household. Acetic acid differs significantly from other caustic poisons, since it has not only a local caustic effect of the coagulative necrosis type, but also has a pronounced resorptive - hemato-nephro- and hepatotoxic effect, which occurs as a result of erythrocyte hemolysis, toxic coagulopathy, and DVT syndrome [3;2].